Historical Transition of Eco-Structure in a Tidal Flat Caused by Expansion of Sewerage Treatment Area - Hideki Tatsumoto; Yuichi Ishii; Motoi Machida; Kazuo Taki (The Scientific World Journal)
An artificial tidal flat was prepared for the mitigation tool on coastal environment. However, it is considered that most of the flat was not restored to the sufficient amenities for aquatic living things, migratory birds, etc. because none of the ecological mechanisms were understood or planned for. It is therefore investigated in this paper that historical transition factors in ecosystem structure are selected and traced with the diffusion of a public sewerage system, and with environmental factors such as water quality, sediment condition, and aquatic producers in the Yatsu Tidal Flat. As a result, it can be defined that the tidal flat, just like a lagoon, was formed artificially with reclamation and development of its circumference at the first step of transition; the water quality and sediment condition gradually became brackish water and muddy sediment conditions, interactively. The ecosystem pyramid forming orderly layers according to trophic level appeared as a high-bio-production potential in its tidal flat. In the second step, i.e., in recent years, the characteristics of water quality and sediment conditions evolved into a foreshore tidal flat, namely, conditions in the flat observed were that the progression of water included a high concentration of chloride ion as seawater and sediment conditions became sandy. Because of that, the inflowing fresh water and organic mater from the land area decreased with the improvement of the public sewerage system. The ecosystem pyramid was distorted into a chaos pyramid, with inversion of Ulva spp.